Preparation of nanocellulose and its potential application - Latifah Jasmania; Wim Thielemans (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2018)
Nanostructured cellulose has received tremendous attention due to its inherent unique properties such as high strength, high surface area, flexible surface chemistry, abundant and renewable. The early polymers industry was nearly completely bio-based and cellulose was one of the most important materials. It has only been the Second World War that changed things and propelled petroleum, as the main source material. Due to global awareness on the use of more green products, cellulose offers an alternative to petroleum-based products. This paper presents the general overview of nanocellulose starting from its cellulose structure and properties to preparation of nanocellulose, properties and its potential application.